Varieties of entrepreneurship: Exploring the institutional foundations of different entrepreneurship types through "Varieties-of-Capitalism" arguments - Selin Dilli; Niklas Elert; Andrea M. Herrmann (Research Institute of Industrial Economics (IFN), 2018)
While entrepreneurship researchers agree that institutions "matter" for entrepreneurship, they also have a rather encompassing understanding of institutions as almost any external factor that influences entrepreneurship. Ultimately, this literature thus comes up with a long list of institutional factors that may explain entrepreneurial differences between countries. But which institutions are most influential? How do these institutions relate to different types of entrepreneurship? And to what extent are institutions complementary to each other in the way they sustain different entrepreneurship types? The literature on "Varieties-of-Capitalism" (VoC) offers a parsimonious theoretical framework to address these questions. Based on the VoC literature, we theoretically derive a consistent set of institutional indicators that can explain differences in entrepreneurship types between countries. Based on principal component and cluster analyses, we illustrate how 21 Western developed economies cluster around four distinct institutional settings. Furthermore, we use simple OLS regressions to show how these institutional constellations are related to different types of entrepreneurship. We conclude that four different "Varieties of Entrepreneurship" can be identified across the Western world. The main implication of our findings is that a "perfect" institutional constellation, equally facilitating different types of entrepreneurship, does not exist. Policy-makers seeking to stimulate entrepreneurship are thus faced with the trade-off of targeting policy reforms to that entrepreneurship type they intend to promote - at the expense of other types of entrepreneurship and the broader societal consequences such reforms will have.
Keywords: L50; M13; O31; P14; 330; Entrepreneurship; Entrepreneurial ecosystems; Varieties-of-Capitalism; Institutional complementarities